Comparison of linear scheduling model and repetitive scheduling method. - Mattila, Kris G. (Journal of construction engineering and management)
Various linear scheduling techniques have been proposed over the years. The limitations on thses techniques have been the inability to determine critical activities. Contractors and departments of transportation have identified the need. Recently two different methods have been proposed - the linear scheduling model and the repetitive scheduling method. This paper discusses basic linear scheduling techniques and then the calculation of critical activities of basic linear scheduling elements using the two methods. The results of the two techniques are compared.